2021
DOI: 10.1093/aobpla/plab008
|View full text |Cite
|
Sign up to set email alerts
|

The dispersal-related traits of an invasive plant Galinsoga quadriradiata correlate with elevation during range expansion into mountain ranges

Abstract: Detecting shifts in trait values among populations of an invasive plant is important for assessing invasion risks and predicting future spread. Although a growing number of studies suggest that the dispersal propensity of invasive plants increases during range expansion, there has been relatively little attention paid to dispersal patterns along elevational gradients. In this study, we tested the differentiation of dispersal-related traits in an invasive plant, Galinsoga quadriradiata, across populations at di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 79 publications
(98 reference statements)
0
10
0
Order By: Relevance
“…Core populations may differ from range‐edge populations both in genetic structure and degrees of plasticity (Berg et al, 2005; Black‐Samuelsson & Andersson, 1997; Stewart & Nilsen, 1995; Volis et al, 2015), but in which direction remains unclear. For example, Liu et al (2021) found that genetic diversity decreased from the core to invading edge in the invasive Asteraceae, Galinsoga quadriradiata in Central China, indicating stronger selection in the core. Mägi et al (2011) found less adaptive plasticity in range‐edge versus core populations of the weed common agrimony Agrimonia eupatoria in southern Estonia.…”
Section: Introductionmentioning
confidence: 99%
“…Core populations may differ from range‐edge populations both in genetic structure and degrees of plasticity (Berg et al, 2005; Black‐Samuelsson & Andersson, 1997; Stewart & Nilsen, 1995; Volis et al, 2015), but in which direction remains unclear. For example, Liu et al (2021) found that genetic diversity decreased from the core to invading edge in the invasive Asteraceae, Galinsoga quadriradiata in Central China, indicating stronger selection in the core. Mägi et al (2011) found less adaptive plasticity in range‐edge versus core populations of the weed common agrimony Agrimonia eupatoria in southern Estonia.…”
Section: Introductionmentioning
confidence: 99%
“…ISSR markers are highly reproducible and accurate tools that generate highly reproducible banding patterns from a single polymerase chain reaction (PCR) amplification ( Raut et al., 2014 ; Stefunova et al., 2014 ). Although newer technique are available, ISRR makers have historically ( Wolfe et al., 1998 ) and recently ( Yan et al, 2019 ; Kwiecińska-Poppe et al., 2020 ; Tang and Ma, 2020 ; Liu et al., 2021 ; Alotaibi and Abd-Elgawad, 2022 ; Flihi et al., 2022 ; Ghanbari et al., 2022 ; Haq et al., 2022 ) been used successfully for diversity studies and structuring of natural populations.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we investigate the role of biotic interactions with AMF communities and native plant competitors in the invasion trajectory of Galinsoga quadriradiata (Asterales: Asteraceae), which is native to tropical America and has been invading China for more than 100 years [ 36 ] in high-elevation mountain ranges in central China. Previous studies of ours indicate that the biomass and dispersal traits of this species change along its elevational range [ 32 , 37 ], leading to extensive invasions in the Qinling and Bashan Mountains [ 9 , 36 ]. Most recently, we showed that AMF beta diversity in soils associated with G. quadriradiata is strongly affected by the elevation at which the soils were collected in the Qinling and Bashan Mountains [ 38 ], supporting that biological interaction strength varies along its invasion trajectory.…”
Section: Introductionmentioning
confidence: 99%